Design and evaluation of the expression of a potential DNA vaccine against Tilapia lake virus (TiLV) - Criollo Joaquin, Mónica Paola (2019)
Tilapia Lake Virus (TiLV) is a pathogen that causes massive mortalities in both cultured and wild tilapia populations around the world. The development of an effective vaccine against this emerging pathogen is imperative to prevent economic losses. In this work an expression vector was designed and evaluated as a potential DNA vaccine against this virus. Initially, a threading analysis was done to predict the three-dimensional structures and functions of the TiLV proteins. Structural homologies were found between the TiLV proteins corresponding to the genomic segment 1 and the genomic segment 4, with the RNA-dependent RNA polymerase proteins of the influenza B virus (56%) and the neuraminidase protein belonging to the influenza A virus capsid (12%), respectively. The PCR product of the viral neuraminidase gene was inserted into the expression plasmid vector pCMV. Finally, the plasmid construct was injected into juveniles of the Nile tilapia Oreochromis niloticus and its expression was measured by real time RT-PCR at 8h, 16h, 24h, and 72h after the second immunizing injection. It was possible to detect gene expression in the four evaluated times and greater expression at 16 hours post injection. These results are the first step in the development of an effective vaccine for the protection of tilapia stocks around the world.